2020
DOI: 10.1108/jaee-10-2019-0199
|View full text |Cite
|
Sign up to set email alerts
|

Board characteristics and foreign equity ownership: evidence from Bangladesh

Abstract: PurposeThe purpose of this study is to examine the effect of board characteristics on foreign equity ownership (FEO) in the listed public limited companies of Bangladesh.Design/methodology/approachThe study collected data from 418 annual reports of listed companies of Bangladesh for the years 2015, 2016 and 2017 to examine the effect of board characteristics on FEO. Ordinary Least Squares (OLS) and Two-Stage Least Squares (2SLS) regression methods are used to test the hypotheses of the study.FindingsThe result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 114 publications
(231 reference statements)
1
8
0
Order By: Relevance
“…Yeh (2018) investigated the association between foreign institutional ownership and board size in Taiwan listed tourism firms and found that board size negatively and significantly influenced the ownership proportion of foreign institutional investors. Similarly, Rashid (2020) found the same result. Thus, the following hypothesis can be stated as following:…”
Section: Hypotheses Developmentsupporting
confidence: 64%
See 4 more Smart Citations
“…Yeh (2018) investigated the association between foreign institutional ownership and board size in Taiwan listed tourism firms and found that board size negatively and significantly influenced the ownership proportion of foreign institutional investors. Similarly, Rashid (2020) found the same result. Thus, the following hypothesis can be stated as following:…”
Section: Hypotheses Developmentsupporting
confidence: 64%
“…Finally, price-to-book value is used as a market performance measure for growth opportunity. Rashid (2020) found significant relationship between foreign ownership and price-to-book value, while Min and Bowman (2015) found no significant impact of price-tobook value in the Korean market.…”
Section: Control Variablesmentioning
confidence: 85%
See 3 more Smart Citations